2017
DOI: 10.1097/md.0000000000007223
|View full text |Cite
|
Sign up to set email alerts
|

Post hoc analyses of East Asian patients from the randomized placebo-controlled PREVAIL trial of enzalutamide in patients with chemotherapy-naïve, metastatic castration-resistant prostate cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
5
19
1
Order By: Relevance
“…Compared with the results of the PREVAIL trial, which focused on treatment of mCRPC before chemotherapy, the number of treatment regimens before ENZ treatment in our trial tended to be relatively high. Kim et al reported that 40% of East Asian patients, and 21% of patients in the overall population of the PREVAIL trial, had received at least two prior antiandrogen therapies . Overall, 52.7% of patients in our pre‐DOC group had received at least two prior antiandrogen therapies.…”
Section: Discussionmentioning
confidence: 76%
“…Compared with the results of the PREVAIL trial, which focused on treatment of mCRPC before chemotherapy, the number of treatment regimens before ENZ treatment in our trial tended to be relatively high. Kim et al reported that 40% of East Asian patients, and 21% of patients in the overall population of the PREVAIL trial, had received at least two prior antiandrogen therapies . Overall, 52.7% of patients in our pre‐DOC group had received at least two prior antiandrogen therapies.…”
Section: Discussionmentioning
confidence: 76%
“…This includes a higher percentage of patients with a Gleason score of ≥8 and a higher percentage with bone disease (likely a result of less frequent PSA testing). However, PREVAIL also found lower median PSA levels and fewer patients with soft tissue disease and bone pain in the East Asian population .…”
Section: Management Of Advanced Prostate Cancer In the Apac Regionmentioning
confidence: 88%
“…Studies in Asian populations (China, Malaysia, Thailand) suggest no difference in safety data for abiraterone or enzalutamide compared with data from global studies. The APAC APCCC 2018 panellists agreed with the APCCC 2017 conclusions that clinical factors, such as performance status, symptoms, comorbidities, disease site, and extent of disease, are important in influencing choice and sequence of treatment.…”
Section: The Apac Apccc 2018 Outcomesmentioning
confidence: 97%
See 2 more Smart Citations